Optimizing the implementation of restorative justice in the settlement of criminal acts in Indonesia - Kandi, Sri; Dinata, Muhammad Ruhly Kesuma; Edrisy, Ibrahim Fikma (Jurnal Idea Hukum, 2025)
Within the criminal court system, restorative justice is a method that emphasizes the improvement of relationships between offenders, victims affected by criminal acts and community involvement in achieving more humane justice. In Indonesia, this idea has been accommodated in various legal policies, but its implementation still faces obstacles, such as regulatory disharmony, lack of understanding of law enforcement officials, and limited community support. Therefore, this article will focus on issues regarding the concept of restorative justice in Indonesia, its legal basis and regulatory policies, the effectiveness of implementation in the perspective of the office of the prosecutor, and strategies to optimize its application.using a statutory and conceptual perspective, normative juridical research methodology is employed. Data was obtained from scientific journals through Google Scholar as well as news from trusted websites such as CNN Indonesia, and Hukum Online. In addition, relevant laws and regulations, such as regulation of the supreme court and the criminal code, and Regulations regarding the office of the attorney general of the republic of indonesia, were systematically reviewed however, official sources. The results showed that from 2020-2023 optimizing the  application of restorative justice experienced a significant increase with 4,443 cases resolved and 111 rehabilitation centers established. Although implemented since 2020 there are still challenges in its implementation. Therefore, the optimization it is necessary for restorative justice to be supported by harmonizing regulations, increasing the capacity of law enforcement officials, and educating the public so that its implementation is more effective in Indonesia’s criminal justice sytem.